Composite metal silicon-carbon negative electrode material and preparation method thereof
By depositing a carbon layer or metal layer on the core layer of silicon carbon material using the MOCVD method to form a composite metal silicon carbon negative electrode material with a core-inner shell-out shell structure, the problems of complex process and instability in the prior art are solved. Efficient cycle performance and conductive performance improvement are achieved.
Patent Information
- Application Number
- CN202411773744.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure CN119252908A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium battery negative electrode materials, and specifically relates to a composite metal silicon carbon negative electrode material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have been widely used due to their high voltage, high specific energy, long cycle life and environmental friendliness. At present, the mainstream commercial use is carbon-based graphite negative electrode materials. However, after continuous research and improvement, traditional graphite negative electrode materials are getting closer and closer to their theoretical capacity of 372mAh / g. In order to meet the needs of higher-capacity lithium batteries, new silicon-based negative electrode materials such as silicon-carbon negative electrodes have been widely studied because their capacity can reach dozens of times that of mainstream graphite negative electrode materials. Currently, CVD (chemical vapor deposition) is the main method for preparing silicon-carbon negative electrode carbon. However, this method is relatively cumbersome. For example, Chinese patent CN105024076A discloses a lithium-ion battery negative electrode material and its preparation method and application. The material is divided into two layers: a carbon core layer and a silicon coating layer. The carbon core layer is coated by the middle silicon layer to form a silicon / carbon composite material. The outer layer of the silicon / carbon composite material is coated with a layer of metal oxide, which can effectively alleviate the expansion of the silicon material, thereby improving the cycle performance of the battery material. Chinese patent CN111326722A discloses a silicon-carbon composite negative electrode material with a core-shell structure and a preparation method, which aims to provide a silicon-carbon composite negative electrode material with a core-shell structure and a preparation method to address the deficiencies of the prior art. The material uses silicon as the main body to provide reversible capacity, and the carbon layer mainly serves as a buffer layer to reduce the volume effect and enhance conductivity. Since the material has a core-shell structure, the volume expansion space caused by silicon during the lithium insertion and de-lithiation process is reserved, which is conducive to promoting the recovery of silicon's volume expansion and improving the cycle performance of the battery.
[0003] At present, the existing technology mainly adopts the process of first atomizing the metal salt solution, and then coating the atomized metal salt solution on the fluidized silicon-carbon composite material to obtain the precursor film. This process is relatively cumbersome and there are many uncontrollable factors in the precursor film, which is not a reliable process. Therefore, it is necessary to develop a new preparation process that can synthesize carbon / metal / silicon composite materials in one go and has stable performance. Summary of the invention
[0004] In view of the above defects or improvement needs of the prior art, the present invention provides a composite metal silicon carbon negative electrode material and a preparation method thereof. The preparation method has the advantages of controllable growth, good coating uniformity and one-time synthesis of carbon / metal / silicon composite materials. The obtained composite metal silicon carbon negative electrode material has good cycle stability.
[0005] In order to achieve the above object, the present invention provides the following technical solutions: The first object of the present invention is to provide a method for preparing a composite metal silicon-carbon negative electrode material, firstly preparing a core layer of the silicon-carbon negative electrode material by a CVD method, and then preparing an inner shell layer and an outer shell layer of carbon by a MOCVD (metal organic compound chemical vapor deposition) method, to obtain a composite metal silicon-carbon negative electrode material having a core-inner shell-outer shell structure; the core layer is a silicon-carbon material; the inner shell layer is a carbon coating layer or a metal film layer; the outer shell layer is a carbon coating layer or a metal film layer.
[0006] Specifically, the steps include: S1. Preparation of the core layer of silicon-carbon negative electrode material: select a carbon base material, dry it and put it into a CVD tube furnace or a fluidized bed CVD reactor, introduce silane at 400°C-700°C for vapor deposition reaction to obtain a silicon-carbon negative electrode material; S2, preparation of carbon coating layer and metal film layer: placing the silicon-carbon negative electrode material obtained in S1 in a MOCVD reactor, evacuating the furnace, introducing carbon source gas at 600°C-1000°C for carbon coating, then introducing inert gas to exhaust the carbon source gas, cooling to 400°C-800°C, introducing metal organic gas for metal film coating, and obtaining a composite metal silicon-carbon negative electrode material; or, The silicon-carbon negative electrode material obtained by S1 is placed in a MOCVD reactor. After the furnace is evacuated, metal organic gas is introduced at 400℃-800℃ for metal film coating, and then inert gas is introduced to evacuate the metal gas. The temperature is raised to 600℃-1000℃ and carbon source gas is introduced for carbon layer coating to obtain a composite metal silicon-carbon negative electrode material.
[0007] The preparation method of the present invention is to first prepare a core layer silicon-carbon material of a silicon-carbon negative electrode material, and then put the core layer silicon-carbon material into an MOCVD device to deposit an inner shell layer and an outer shell layer in sequence, wherein the inner shell layer and the outer shell layer can be randomly selected from a carbon layer / metal layer or a metal layer / carbon layer, and metal organic gas, carbon source gas, and inert gas are introduced through a pipeline connected to the MOCVD device, and various reaction conditions are matched to obtain a uniformly coated composite metal silicon-carbon negative electrode material. The metal film layer coated by the method can not only effectively improve the shortcoming of easy expansion of the silicon-carbon material, but also can be used as a good conductive material to improve the cycle performance of the battery. Compared with the existing technology, it has the advantages of controllable growth, good coating uniformity, and can synthesize carbon / metal / silicon composite materials at one time, optimizes the synthesis process, and the prepared silicon-carbon negative electrode material has more stable cycle performance.
[0008] Furthermore, in the above technical solution S1, the carbon-based material is any one of natural graphite, few-layer graphene, and carbon nanofibers; and the drying method of the carbon-based material is: baking the carbon-based material at 120°C-180°C for 12h-18h.
[0009] Furthermore, in the above technical solution S1, the flow rate of silane is 50sccm / min-300sccm / min, and the introduction time is 30min-240min; the thickness of the silicon-carbon negative electrode material is 30nm-200nm, of which the silicon film thickness is 10nm-100nm, and the carbon film thickness is 20nm-200nm.
[0010] Furthermore, in the above technical solution S2, the carbon source gas is any one of methane, acetylene, and ethylene; the metal organic gas is any one of triethylaluminum, trimethylaluminum, and molybdenum hexacarbonyl; and the inert gas is any one or more of nitrogen, argon, and helium.
[0011] Furthermore, in the above technical solution S2, the amount of the inert gas introduced is 1 to 10 times the volume of the carbon source gas.
[0012] Furthermore, in the above technical solution S2, the coating amount of the metal film layer is 1%-2% of the mass of the silicon-carbon negative electrode material.
[0013] Furthermore, in the above technical solution S2, after the furnace is evacuated, the temperature is controlled at 700°C-900°C when the carbon source gas is introduced; and the temperature is controlled at 500°C-700°C when the metal organic gas is introduced.
[0014] Furthermore, in the above technical solution S2, the flow rate of the carbon source gas is 0.5L / min-5L / min.
[0015] The second object of the present invention is to provide a composite metal silicon carbon negative electrode material prepared by the above preparation method.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts CVD method to first prepare the core layer silicon-carbon material of the silicon-carbon negative electrode material, and then creatively uses MOCVD method to deposit carbon layer / metal layer or metal layer / carbon layer on the surface of the core layer. By connecting multiple pipelines on the MOCVD equipment, metal organic gas, carbon source gas and inert gas are respectively introduced and each reaction condition is controlled, so that carbon / metal / silicon composite material can be synthesized in a MOCVD reactor at one time. This method has the characteristics of controllable growth and good coating uniformity. The coated metal film layer can effectively improve the shortcoming of easy expansion of silicon-carbon material, and can also be used as a good conductive material to improve the cycle performance of the battery, with excellent performance and long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 This is a scanning electron microscope image of the composite metal silicon carbon negative electrode material of Example 2 of the present invention; Figure 2 This is a scanning electron microscope image of the composite metal silicon carbon negative electrode material of Comparative Example 1 of the present invention; Figure 3 This is a perspective electron microscope image of the composite metal silicon carbon negative electrode material of Example 2 of the present invention; Figure 4 This is a perspective electron microscope image of the composite metal silicon carbon negative electrode material of Comparative Example 1 of the present invention; Figure 5 This is a comparison diagram of the capacity decay curve of the present invention. DETAILED DESCRIPTION
[0019] The experimental methods in the following examples are conventional methods unless otherwise specified. The raw materials involved in the following examples are common commercial products and can be purchased from the market unless otherwise specified.
[0020] The above-mentioned technical features of the present invention and the technical features specifically described below (such as implementation cases) can be combined with each other to form a new or preferred technical solution.
[0021] The raw materials involved in the embodiments of the present invention are either existing commercially available products or can be prepared according to existing methods, and the testing methods are industry methods.
[0022] Example 1 A method for preparing a composite metal silicon carbon negative electrode material comprises the following specific steps: S1. Preparation of the core layer of silicon-carbon negative electrode material: natural graphite is selected as the carbon base material, the carbon base material is placed at 120°C for 18 hours, and after drying, it is placed in a CVD tube furnace or a fluidized bed CVD reactor, and silane with a flow rate of 300 sccm / min is introduced at 400°C for 100 minutes to perform a vapor deposition reaction to obtain a silicon-carbon negative electrode material with a thickness of 60nm, wherein the silicon film thickness is 20nm and the carbon film thickness is 40nm; S2. Preparation of carbon coating layer and metal film layer: The silicon-carbon negative electrode material obtained in S1 is placed in a MOCVD reactor. After the furnace is evacuated, ethylene carbon source gas with a flow rate of 1L / min is introduced at 850°C for carbon layer coating. Subsequently, helium inert gas with a volume twice that of the carbon source gas is introduced to evacuate the carbon source gas. After the temperature is lowered to 500°C, triethylaluminum metal organic gas is introduced for metal film coating, wherein the coating amount of the metal film layer is 1.5% of the mass of the silicon-carbon negative electrode material to obtain a composite metal silicon-carbon negative electrode material.
[0023] Example 2 A method for preparing a composite metal silicon carbon negative electrode material comprises the following specific steps: S1. Preparation of the core layer of silicon-carbon negative electrode material: select few-layer graphene as the carbon base material, bake the carbon base material at 150°C for 16 hours, put it into a CVD tube furnace or a fluidized bed CVD reactor after drying, and pass silane at a flow rate of 150 sccm / min for 200 minutes at 500°C to perform a vapor deposition reaction to obtain a silicon-carbon negative electrode material with a thickness of 100 nm, wherein the silicon film thickness is 30 nm and the carbon film thickness is 70 nm; S2. Preparation of carbon coating layer and metal film layer: The silicon-carbon negative electrode material obtained in S1 is placed in a MOCVD reactor. After the furnace is evacuated, trimethylaluminum metal organic gas is introduced at 600°C for metal film coating, wherein the coating amount of the metal film layer is 1.5% of the mass of the silicon-carbon negative electrode material. Subsequently, argon inert gas is introduced to evacuate the metal gas, and the temperature is raised to 900°C, and acetylene carbon source gas at a flow rate of 2L / min is introduced for carbon layer coating to obtain a composite metal silicon-carbon negative electrode material.
[0024] Example 3 A method for preparing a composite metal silicon carbon negative electrode material comprises the following specific steps: S1. Preparation of the core layer of silicon-carbon negative electrode material: Select carbon nanofiber as the carbon base material, bake the carbon base material at 180°C for 12 hours, put it into a CVD tube furnace or a fluidized bed CVD reactor after drying, and pass silane at a flow rate of 50 sccm / min for 240 minutes at 700°C to perform a vapor deposition reaction to obtain a silicon-carbon negative electrode material with a thickness of 150 nm, wherein the silicon film thickness is 50 nm and the carbon film thickness is 100 nm; S2. Preparation of carbon coating layer and metal film layer: The silicon-carbon negative electrode material obtained in S1 is placed in a MOCVD reactor. After the furnace is evacuated, a methane carbon source gas with a flow rate of 3L / min is introduced at 900°C for carbon layer coating. Subsequently, nitrogen inert gas with a volume 4 times that of the carbon source gas is introduced to evacuate the carbon source gas. After the temperature is lowered to 550°C, molybdenum hexacarbonyl metal organic gas is introduced for metal film coating, wherein the coating amount of the metal film layer is 2% of the mass of the silicon-carbon negative electrode material to obtain a composite metal silicon-carbon negative electrode material.
[0025] Comparative Example 1 A method for preparing a silicon-carbon negative electrode material, which differs from Example 3 in that, in S2, the silicon-carbon negative electrode is coated with a carbon layer by a CVD method and with a metal film layer by a metal salt solution method to obtain a composite silicon-carbon negative electrode material.
[0026] Test example 1. Compare the electron microscope images of the composite metal silicon carbon negative electrode materials prepared in Example 2 and Comparative Example 1. Figure 1 and Figure 3 The scanning electron microscope image and transmission electron microscope image of the composite metal silicon carbon negative electrode material obtained in Example 2 are shown in FIG. Figure 2 and Figure 4 The scanning electron microscope and transmission electron microscope images of the composite metal silicon-carbon negative electrode material obtained in comparative example 1. It can be seen that the particle morphology in Example 2 is more regular, the agglomeration is more dispersed, the surface roughness and pore structure are more reasonable, and its lattice fringes are more clearly displayed, the crystal defects are slightly less, and the silicon-carbon phase interface is more uniformly and clearly distributed, which can reduce the volume expansion of silicon during the charge and discharge process.
[0027] 2. The performance of the silicon-carbon negative electrode materials prepared in Examples 1 to 3 and Comparative Example 1 was tested. The results are shown in Table 2, where the performance test conditions of Table 1 are shown in Table 1.
[0028] Table 1 Performance test conditions
[0029] Table 2 Comparison of buckle performance
[0030] From the results in Table 2, it can be seen that the composite metal silicon-carbon negative electrode material prepared by the preparation method of the present invention has a higher specific capacity, the first efficiency is above 85%, and the capacity residual rate after 500 cycles is still above 89%, and the cycle performance is stable. In Comparative Example 1, the carbon layer of the silicon-carbon negative electrode is coated by CVD method and the metal film layer is coated by metal salt solution method. Not only is the process complicated, it requires two steps to obtain the carbon-coated / metal-coated composite metal silicon-carbon negative electrode material, and its specific capacity and first efficiency are significantly lower, and the cycle stability is worse. The capacity residual rate after 500 cycles is only 79%. From the capacity attenuation curve comparison chart ( Figure 5 ) It can also be seen that the composite metal silicon-carbon negative electrode material obtained by the present invention has better cycle performance, especially in Example 2, the capacity remaining rate is still 92% after 500 cycles, and the cycle stability is good.
[0031] In summary, the present invention first prepares the core layer silicon-carbon material of the silicon-carbon negative electrode material, and then uses the MOCVD method to deposit a carbon layer / metal layer or a metal layer / carbon layer on the surface of the core layer at one time. The process is simpler, the growth is controllable, and the coating is uniform. The obtained silicon-carbon negative electrode material has high specific capacity and first efficiency, and the cycle performance is more stable, which improves the service life of the lithium-ion battery.
[0032] Finally, it should be emphasized that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a composite metal silicon carbon negative electrode material, characterized in that: The core layer of the silicon-carbon negative electrode material is first prepared by the CVD method, and then the inner shell layer and the outer shell layer carbon are prepared by the MOCVD method to obtain a composite metal silicon-carbon negative electrode material with a core-inner shell-outer shell structure; the core layer is a silicon-carbon material; the inner shell layer is a carbon coating layer or a metal film layer; the outer shell layer is a carbon coating layer or a metal film layer.
2. The preparation method according to claim 1, characterized in that: The specific steps include: S1. Preparation of the core layer of silicon-carbon negative electrode material: select a carbon base material, dry it and put it into a CVD tube furnace or a fluidized bed CVD reactor, introduce silane at 400°C-700°C for vapor deposition reaction to obtain a silicon-carbon negative electrode material; S2, preparation of carbon coating layer and metal film layer: placing the silicon-carbon negative electrode material obtained in S1 in a MOCVD reactor, evacuating the furnace, introducing carbon source gas at 600°C-1000°C for carbon coating, then introducing inert gas to exhaust the carbon source gas, cooling to 400°C-800°C, introducing metal organic gas for metal film coating, and obtaining a composite metal silicon-carbon negative electrode material; or, The silicon-carbon negative electrode material obtained by S1 is placed in a MOCVD reactor. After the furnace is evacuated, metal organic gas is introduced at 400℃-800℃ for metal film coating, and then inert gas is introduced to evacuate the metal gas. The temperature is raised to 600℃-1000℃ and carbon source gas is introduced for carbon layer coating to obtain a composite metal silicon-carbon negative electrode material.
3. The preparation method according to claim 2, characterized in that: In S1, the carbon-based material is any one of natural graphite, few-layer graphene, and carbon nanofibers; and the drying method of the carbon-based material is: baking the carbon-based material at 120° C.-180° C. for 12 h-18 h.
4. The preparation method according to claim 2, characterized in that: In S1, the flow rate of silane is 50sccm / min-300sccm / min, and the introduction time is 30min-240min; the thickness of the silicon-carbon negative electrode material is 30nm-200nm, of which the silicon film thickness is 10nm-100nm, and the carbon film thickness is 20nm-200nm.
5. The preparation method according to claim 2, characterized in that: In S2, the carbon source gas is any one of methane, acetylene, and ethylene; the metal organic gas is any one of triethylaluminum, trimethylaluminum, and molybdenum hexacarbonyl; and the inert gas is any one or more of nitrogen, argon, and helium.
6. The preparation method according to claim 2, characterized in that: In S2, the amount of the inert gas introduced is 1 to 10 times the volume of the carbon source gas.
7. The preparation method according to claim 2, characterized in that: In S2, the coating amount of the metal film layer is 1%-2% of the mass of the silicon-carbon negative electrode material.
8. The preparation method according to claim 2, characterized in that: In S2, after the furnace is evacuated, the temperature is controlled at 700°C-900°C when the carbon source gas is introduced; the temperature is controlled at 500°C-700°C when the metal organic gas is introduced.
9. The preparation method according to claim 2, characterized in that: In S2, the flow rate of the carbon source gas is 0.5 L / min-5 L / min.
10. A composite metal silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Anode material for lithium-ion battery and preparation method and application of anode material
CN105024076A
Silicon-carbon composite negative electrode material with core-shell structure and preparation method
CN111326722A
Silicon-based composite material with nano hierarchical structure and preparation method and application of silicon-based composite material with nano hierarchical structure
CN108023074A
Silicon-carbon composite negative electrode material and preparation method and application thereof
CN114068901A
Graphite protected anode active material particles for rechargeable lithium batteries
US20200212426A1
